PENERAPAN METODE AHP DAN TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN KINERJA GURU DI SMPN 3 JEKULO - Renisa Ramadhani (LPPM Universitas Abdurrab, 2026)
Teacher performance assessment in schools needs to be conducted objectively, measurably, and in an integrated manner so that the evaluation results can be used as a basis for decision making. SMP Negeri 3 Jekulo Kudus requires a system capable of processing several assessment indicators, such as student questionnaires, student learning outcomes, principal assessments, and teacher attendance. This study aims to build a web-based decision support system to determine teacher performance rankings using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The AHP method is used to determine the weight of each criterion, while TOPSIS is used to calculate preference scores and determine teacher rankings. Data were obtained through interviews, observations, questionnaires, literature studies, and documentation. The AHP weighting results show that the student questionnaire criterion has the highest weight of 0.4658, followed by student scores of 0.2771, principal assessment of 0.1611, and teacher attendance of 0.0960. The Consistency Ratio value of 0.0115 indicates that the criteria weights are consistent. The TOPSIS results show that the first rank obtained a preference score of 0.8411. The system developed is capable of displaying rankings, preference scores, validating results, and providing recommendations for improving teacher performance. Thus, this system can assist schools in conducting teacher performance evaluations more quickly, transparently, and objectively.